تطوير التقييم الأصيل المتكامل لمهارات التحدث العربية في التعليم الثانوي للصف الثامن وزارة الأوقاف 2019: Development of Integrated Authentic Assessment in Speaking Skills Grade 8 Arabic Textbook Ministry of Religious Affairs 2019 - Siska Qurrota A'yun; R. Umi Baroroh; Azizah Nur Fitri Aeni (Journal of Arabic Language Teaching, 2025)
This study aims to analyze and address assessment challenges, particularly in speaking skills, within the 2019 Kemenag Arabic Class VIII textbook published by the Ministry of Religious Affairs of Indonesia (Kemenag RI). Employing a descriptive qualitative method and literature review, data were gathered through descriptive analysis followed by in-depth interpretation. The research proposes an innovative solution by implementing authentic assessment to overcome existing evaluation issues. Specifically, the study focuses on revising and enhancing Arabic language learning questions across six chapters of a high school-level textbook, utilizing an integrative and authentic approach. Revisions targeted various question types related to the kalām (speaking) skill, emphasizing oral proficiency improvement through project-based activities such as presentations, video recordings, and direct dialogues. Each question was contextualized to reflect real-life communication, enabling students to express personal experiences and perspectives actively. The revisions led to a notable shift from passive questioning to active, participatory tasks, thereby fostering integration across multiple language skills. Consequently, this innovation reinforces an integrative learning framework and facilitates the development of more functional and practical Arabic language competencies.